Hybrid renewable energy systems for a remote community in a high mountain plateau - Mahmud S.; Kaihan M.K.; Salehin S.; Ferdaous M.T.; Nasim M. (Institute for Ionics, 2023)
Electric energy storage; Sensitivity analysis; Solar power generation; Afghanistan; Energy systems; Hybrid optimization; Hybrid optimization model for electric renewable; Hybrid renewable energies; Hybrid renewable energy system; Off-grid electrification; Optimization models; Remote communities; Renewable energies; Renewable energy resources